Metaforiskie hidronīmi Latvijā - Balode, Laimute (Baltistica, 2012)
METAPHORIC HYDRONYMS IN LATVIASummaryA metaphor – a term or phrase applied to something which it is not literally applicable to – usually constructs an analogy between two things. This creates associative perception. There are quite a few Latvian toponyms as well as hydronyms made on the basis of indirect comparison: Latv. lake-names Āķis ʻcrook, hookʼ, Panna ʻfrying-panʼ, Baļļa ʻtubʼ may stress the configuration of the hydroobject, Latv. river-name Adatiņa ʻneedleʼ describes the stream of the brook. There are many more compound hydronyms and multi-word names which could be perceived as metaphorical: Latv. lake-names Garasts ʻlong taleʼ, Velna acs ʻDevilʼs eyeʼ, etc.Metonymical hydronyms are names of objects in one or another way associated with hydroobjects, e.g. Latv. lake-name Zuosins ‘gander’, Dunkurs ‘net’. Another possible way of coining hydronyms is synecdoche, i.e. using the name of a part of some object as the name of the whole object, for example, Pakavlīcis ʻhorseshoe bay’ – the bay name which is used as the name of the lake. Metaphor, metonymy and perhaps synecdoche in toponymy, particularly in hydronymy, are still an unexplored field of Baltic onomastics.
Keywords: Latvian; metaforic hydronyms; onomastics